Finite-Time Adaptive Control of Nonstrict-Feedback Nonlinear Systems With Time-Varying Full State Constraints - Jiahuan Lv; Rui Zhang; Junmin Li; Jianmin Jiao; Yuan Cheng; Xuejie Yang (IEEE Access)
This paper proposes a finite-time adaptive tracking fuzzy control approach for nonlinear nonstrict-feedback systems with unknown disturbances and time-varying full state constraints. The fuzzy logic system is used to approximate the unknown nonlinear function, and the tan-type barrier technique is used to keep all states inside a predetermined region. The adaptive fuzzy controller is formulated utilizing the barrier Lyapunov functions (BLFs) and the backstepping approach. This guarantees that all the signals in the closed loop are bounded, and the system reaches stability in a finite amount of time while complying with the time-varying full state constraints, and the tracking error varies within the predefined compact range around zero. Finally, the efficacy of the proposed method is exemplified via a simulation example.